(3JGQjN GdESdGe hWHbGJ GdeTGgjQ hGdCYdGes - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg (B: (3ddEeGe CMeO hJGQN GdeaVd Hf ZSGf GdZdGHi hGdLQM hGdJYOjd Yf jMji Hf jMji hGdLQM hGdJYOjd dYHO GdQMef Hf CHj MGJe s
(3BNQgG (B:s
(3SeYJ YdjkG QVi Gddg Yfg jbhd SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd NjQ JSGAgG NOjNI HfJ NhjdO hNjQ fSGAgG eQje HfJ YeQGf CNQLg eSde hGddg CYde s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs